Significance of sequence variation in the P1 and 3A genes of foot-and-mouth-disease virus isolates from southern Africa - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc Agric (Microbiology))--University of Pretoria, 2006.